1982
DOI: 10.1038/bjc.1982.270
|View full text |Cite
|
Sign up to set email alerts
|

Doubling time of circulating cea and its relation to survival of patients with recurrent colorectal cancer

Abstract: Summary.-In a retrospective study the postoperative time courses of CEA in colorectal cancer patients with recurrent disease were analysed. In 87/114 cases with increasing concentrations of circulating CEA under close follow-up a linear relationship between log CEA and time could be established during disease recurrence. The individual doubling times of the serum CEA concentration in the log CEA period were calculated and found to cover distinct ranges dependent on the diagnosis of disease recurrence. The CEA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 6 publications
4
22
0
2
Order By: Relevance
“…Similarly, serial studies of sporadic colorectal tumor patients have indicated that the transition from large adenoma to carcinoma takes Ϸ15 years (11). Our estimates are also consistent with the long doubling times of tumors determined by serial radiologic studies or serial measurements of the CEA serum biomarker (10,12,32,33). Such studies have indicated mean doubling times that are generally 2-4 months in metastases and much longer in adenomas and carcinomas.…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, serial studies of sporadic colorectal tumor patients have indicated that the transition from large adenoma to carcinoma takes Ϸ15 years (11). Our estimates are also consistent with the long doubling times of tumors determined by serial radiologic studies or serial measurements of the CEA serum biomarker (10,12,32,33). Such studies have indicated mean doubling times that are generally 2-4 months in metastases and much longer in adenomas and carcinomas.…”
Section: Discussionsupporting
confidence: 75%
“…There was a close correlation between survival and CEA doubling times for untreated liver metastasis. CEA doubling line has been claimed to be a good index of tumour growth rate (Stabb et al, 1982). In our study, we found that the CEA doubling times in hCG-positive large bowel cancers were significantly shorter than those in hCG-negative cancers, suggesting that hCG-positive carcinomas have higher proliferative activity and higher growth rates.…”
Section: Discussionsupporting
confidence: 48%
“…Thereafter, serum CEA-dt level was also reported to strongly correlate with the survival of patients with recurrent colorectal cancer [21]. Onodera et al [31] reported that CEA-dt reflects the rate of growth and is the most powerful determinant, while it also correlates with survival, more closely than the CEA level.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al [20] reported that the tumor doubling time of a liver metastasis from colorectal cancer was the most reliable risk factor for postoperative recurrence in the remnant liver and poor prognosis. Staab et al [21] stated that doubling time of carcinoembryonic antigen (CEA-dt) was strongly correlated with tumor doubling time. Koga et al [22] reported that CEA-dt is a prognostic factor after a hepatectomy of liver metastasis from colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%